Study of the Brand Resonance among Patients Hospitalized in Al-Madina Private Hospital in Mosul City - Abdullah, Anis A.; Abdulnabi, Shuaib M. (PROSPECTIVE RESEARCHES, 2024)
The main aim of this research is to verify the possesses of brand resonance factors among patients benefiting from the researched hospital services. The current research used the descriptive analytical method to describe the research variables and the nature of the relationship between them. Primary data was collected using a questionnaire that was distributed to (60) (patients receiving treatment during the period of conducting the research) at Al-Medina Private Hospital, and the research hypothesis was tested using methods appropriate statistics. One of the most important findings of this research is that the researched hospital has brand resonance factors among patients hospitalized, but at varying levels. This research is considered one of the pioneering study in the field of health marketing locally and in the Arab world. The researchers employed the factors of brand resonance in a private hospital as a brand that can resonate with the patients receiving treatment there.